Tifton 419 Bermudagrass (Cynodon dactylon C. transvaaliensis) response to plant grow inhibitors - Marchi, Sidnei Roberto de; Martins, Dagoberto [UNESP]; Costa, Neumárico Vilanova da (My University, 2014)
Tifton 419' bermudagrass cultivar [Cynodon dactylon (L.) Pers. x C. transvaalensis Burtt-Davy] is the most preferred turfgrass for sportive, commercial and residential lawns. On similar species, such as Stenotaphrum secundatum and Zoysia japonica, gibberellic acid-inhibiting plant growth regulators (PGRs) are used to decrease mowing frequency. A very limited research has been reported yet on the PGRs regarding seasonal effects of single vs. multiple applications of these products on turfgrass quality and clipping production on South America. This study aimed to evaluate the effect of sequential applications of different plant growth inhibitors during re-growth and flower rachis emission of 'Tifton 419' Bermudagrass. The treatment pattern includes an initial application followed by one sequential application at 14 days intervals, according to the following: prohexadione-calcium at 100+100 or 200+200 g a.i. ha-1, bispyribac-sodium at 40+40 or 60+60 g a.i. ha-1, trinexapac-ethyl at 113+113, 226+113, 226+226, 452+113, 452+226, 452+452, 678+0 or 904+0 g a.i. ha-1, and untreated control. The treatment effect was evaluated based on measurements of visual injury, height of plants, height and number of flower rachis, and clipping total dry mass production. The results showed that only bispyribac-sodium provided visual injury on 'Tifton 419' Bermudagrass, but the symptoms quickly tend towards zero at 21 days after second application (DASA). 'Tifton 419' Bermudagrass greens could be better handle by sequential application of trinexapac-ethyl, or prohexadione-calcium or bispyribac-sodium, once the height of plants, seedhead emission and total clipping dry mass reduction were over than 37%, 91% and 88%, respectively, for a period up to 60 DASA.